Development Of Conceptual Information Systems Framework Using Grounded Theory - Raja Ikram, Raja Rina; Abd Samad, Rosleen; Salahuddin, Lizawati; Abd Ghani, Mohd Khanapi; Ab Hamid, Raihan (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
This paper shall present a research protocol to develop a conceptual framework in the information systems field using grounded theory method. The research protocol presented is an exploratory research using qualitative methods. The grounded theory based study was conducted via healthcare experts in the field of modern medicine, Traditional Malay Medicine, and information technology subject matter experts. A conceptual framework was initially proposed from the literature review and analysis of interviews of the current framework. The conceptual framework was then validated via healthcare practitioners and IT industry experts. A prototype system of electronic health record was also examined by the respondents to validate the proposed conceptual framework via exploratory prototyping. Consequently, the validation findings were analysed and new themes that emerged from the findings was highlighted to be included in the revised framework.